2022
DOI: 10.1053/j.semnuclmed.2021.06.017
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT of COVID-19 and Other Lung Infections

Abstract: While not conventionally used as the first-line modality, [ 18 F]-2-fluoro-2-deoxy-D-glucose (FDG) - positron emission tomography/computed tomography (PET/CT) can identify infection and inflammation both earlier and with higher sensitivity than anatomic imaging modalities [including chest X-ray (CXR), computed tomography (CT), and magnetic resonance imaging (MRI)]. The extent of inflammation and, conversely, recovery within the lungs, can be roughly quantified on FDG-PET/CT using maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 88 publications
2
34
0
Order By: Relevance
“…Making use of PET/CT in detection of asymptomatic COVID-19 infections in these patients provides an added benefit beyond its oncological aim. 27 Few studies also showed the importance of the application of hygienic measures, contact minimisation, and usage of personal protective equipment for the safety and protection of the health personnel as well as patients. 28 Another important aspect to be noted is that, once the findings are detected, appropriate action and treatment can be undertaken with clinical monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Making use of PET/CT in detection of asymptomatic COVID-19 infections in these patients provides an added benefit beyond its oncological aim. 27 Few studies also showed the importance of the application of hygienic measures, contact minimisation, and usage of personal protective equipment for the safety and protection of the health personnel as well as patients. 28 Another important aspect to be noted is that, once the findings are detected, appropriate action and treatment can be undertaken with clinical monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Findings on PET/CT in these early reports described heterogeneous or diffuse FDG uptake in ground glass opacities and consolidation, predominantly with a subpleural distribution ( Figure 1 ). 10 , 11
Figure 1 62-year-old male patient with history of lymphoma underwent PET/CT scan for restaging. PET maximum intensity projection (MIP) images (A,D) and axial PET/CT fusion images (B) shows hypermetabolic bilateral predominantly subpleural areas (arrows) with the highest SUV max of 8.7, corresponding to ground glass opacities and solid consolidations on the axial low dose CT scan.
…”
Section: Molecular Imaging In Covid-19 Detection and Complicationsmentioning
confidence: 99%
“…but also assess the extent of disease and follow up to assess residual infection status [27]. Recently, 18F-FDG-labeled leukocyte scan has been used to aid in the diagnosis of disseminated mucormycosis (pulmonary and intestinal) in a post-COVID-19 patient with other co-morbidities, including diabetes mellitus and post renal transplant status.…”
Section: Histopathology Microscopy and Culturesmentioning
confidence: 99%
“…FDG PET/CT can be a particularly useful modality in patients with multiple risk factors for invasive fungal disease (IFD), to not only diagnose pulmonary fungal infections but also assess the extent of disease and follow up to assess residual infection status [ 27 ]. Recently, 18F- FDG–labeled leukocyte scan has been used to aid in the diagnosis of disseminated mucormycosis (pulmonary and intestinal) in a post-COVID-19 patient with other co-morbidities, including diabetes mellitus and post renal transplant status.…”
Section: Diagnosismentioning
confidence: 99%